Innovation interactions: Multinational spillovers and local absorptive capacity - Ronald B. Davies; Mahdi Ghodsi; Francesca Guadagno (The Vienna Institute for International Economic Studies (wiiw), 2025)
The hope that multinational firms will improve local employment and productivity is a driving force behind policy efforts to attract investment. Such spillovers are often motivated by technological spillovers from foreign to domestic firms. We address this possibility by using the patenting activity of foreign multinationals in Europe as a measure of affiliate activity alongside more traditional proxies. We find that local firms' employment and labour productivity is higher when FDI activity increases, particularly when those multinationals are upstream of locals. Furthermore, this effect is particularly significant among domestic patenting firms. Thus, it seems that the benefits of inbound investment are greatest for local innovators who are exposed to inbound innovating foreigners.
Keywords: F23; O24; O33; O34; Q55; 330; spillovers; Foreign Direct Investment; Patents